2018
DOI: 10.1016/j.seizure.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Are epilepsy patients bypassing primary care? A cross-sectional study from India

Abstract: Many epilepsy patients seeking tertiary care do not need it. Access and quality of epilepsy care can be improved if there is a rational and need-based distribution of patients between primary, secondary and tertiary care. Referral systems also need to be developed and used to transition patients from one level of care to another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Despite recent government efforts to encourage use of primary care through the removal of user fees, primary care bypassing is extremely common in Lusaka, and Level 1 and Level 3 hospitals are used extensively for non-emergency care. These findings are consistent with a growing literature showing high rates of bypassing in low- and middle-income countries [ 20 34 , 36 , 37 , 45 48 ]. Our study builds on the existing literature by mapping bypassing patterns in an urban setting.…”
Section: Discussionsupporting
confidence: 93%
“…Despite recent government efforts to encourage use of primary care through the removal of user fees, primary care bypassing is extremely common in Lusaka, and Level 1 and Level 3 hospitals are used extensively for non-emergency care. These findings are consistent with a growing literature showing high rates of bypassing in low- and middle-income countries [ 20 34 , 36 , 37 , 45 48 ]. Our study builds on the existing literature by mapping bypassing patterns in an urban setting.…”
Section: Discussionsupporting
confidence: 93%
“…As discussed in a previous paper, at least 40% of these patients did not actually need tertiary care. [ 15 ] Yet, we found that a significant proportion of patients were already on polytherapy—85% in the non-adherent group and 43% in the adherent group. Excessive, often irrational use of polytherapy reflects a lack of standardization of prescribing practices for epilepsy in the country.…”
Section: Discussionmentioning
confidence: 79%
“…Adherence data were collected during the course of a single center, cross-sectional study conducted at a tertiary care teaching hospital that provides comprehensive epilepsy care in New Delhi, India. [ 15 ] While consecutive epilepsy patients presenting to the Neurology outpatient clinic for the first time had been enrolled in the original study, only those patients who were 18 years or older were included to study adherence. We excluded younger patients as a self-reported scale was being used to assess adherence and reliability in younger patients was uncertain.…”
Section: Ethodsmentioning
confidence: 99%
“…A skewed distribution of specialist doctors with hardly any specialist care available outside of few large metropolitan cities is a serious bottleneck that is difficult to address. We have earlier documented this gap in epilepsy primary and secondary care [12]. A viable option may be to conduct more outreach clinics in the least served communities.…”
Section: Discussionmentioning
confidence: 96%